Hybrid nanocellulose/f-MWCNTs nanocomposite for the electrochemical sensing of diclofenac sodium in pharmaceutical drugs and biological fluids - Shalauddin, Md; Akhter, Shamima; Basirun, Wan Jefrey; Bagheri, Samira; Anuar, Nadzirah Sofia; Johan, Mohd Rafie (Elsevier, 2019)
A nanocomposite from a green nanomaterial (nanocellulose) and f-MWCNTs was modified onto glassy carbon (GC) electrode for the detection of diclofenac sodium (DCF), a non-steroidal anti-inflammatory drug (NSAID) and widely used electroactive painkiller. The presence of OH groups in the nanocellulose provides more binding sites for different analytes. This ensures an axial modulus rearrangement and the incorporation of f-MWCNTs which provides larger surface area, high mechanical strength and improved electrical conductivity. On the other hand, the synergy between both compounds enhances the electrochemical detection of DCF in human blood and urine. Under optimum conditions, the modified electrode exhibited a remarkable improvement in the anodic peak current (41.6 μA) for 50 μM DCF at 0.677 V peak potential. The newly fabricated electrode showed two linear dynamic ranges from 0.05 to 1.00 μM and 2–250 μM DCF with low detection limit of 0.012 μM. In addition, differential pulse voltammetry (DPV) and cyclic voltammetry (CV) showed good sensitivity and selectivity for the determination of DCF. With this technique, the modified electrode was very effective and suitable for DCF determination from commercial tablets, ampoules (pharmaceutical preparations) and also from clinical preparations (human blood serum and urine sample) with good recoveries. © 2019 Elsevier Ltd